Chemical composition, antioxidant and antimicrobial activities of stem barks of Englerina gabonensis Engler and Sterculia tragacantha Lindl from Gabon - Cédric SIMA OBIANG; Rick-Léonid Ngoua-Meye-Misso; Guy-Roger Ndong-Atome; Joseph-Privat Ondo; Louis-Clément Obame-Engonga; Edouard Nsi-Emvo (International Journal of Phytomedicine, 2017)
Aim of this work was to evaluate the phytochemical constituents, antioxidant and antimicrobial potential of water-acetone, water-ethanol and water extracts of Englerina gabonensis and Sterculia tragacantha.Presence of phenols was evaluated to estimate the effects of plants on microbial diseases. Water-acetone, water-ethanol and water extracts were examined for antioxidant activities. All plant extracts were tested against six reference strains, eleven clinical isolates and two fungal strains. Phenolic content were highest in the water-acetone and water-ethanol extracts from Englerinagabonensis in comparison with Sterculia tragacantha.The AAI (Antioxidant Activity Index)of water-acetone and water-ethanol extracts of Englerina gabunensis are superiors with 2. Plant extracts of Sterculia tragacantha show weak antioxidant activity (AAI < 0.5).The aqueous extract of Englerina gabonensis has a bactericidal effect on Salmonella Spp. Water-ethanol extract is bactericidal on Bacillus cereus LMG 13569 BHI, Salmonella Sppand Neisseria meningitides. Water-acetone extract presents a bactericidal activity on Enterococcus faecalis103907 CIP, Escherichi coli, Staphylococcus aureus, Acinetobacter baumanniiand Neisseria meningitides. Our results suggest that Englerina gabonensis extracts contain greater antioxidant and antimicrobial properties than Sterculia tragacantha extracts.